2009
DOI: 10.1002/anie.200902543
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels and Aerogels from Noble Metal Nanoparticles

Abstract: Aerogels are fine inorganic superstructures with enormously high porosity and are known to be exceptional materials with a variety of applications, for example in the area of catalysis. [1] The chemistry of the aerogel synthesis originated from the pioneering work [2] from the early 1930s and was further developed starting from the 1960s. [1,3] Attractive catalytic, thermoresistant, piezoelectric, antiseptic, and many other properties of the aerogels originate from the unique combination of the specific proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
351
3
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 287 publications
(367 citation statements)
references
References 45 publications
(48 reference statements)
8
351
3
3
Order By: Relevance
“…However, the fabrication methods for these kinds of structures are tedious and intrinsically limited, thus calling for novel preparation methods that could be applied to other metallic NCs. A way to overcome these problems could be hydro-or aerogelation of metals and metal oxides [14][15][16][17][18]. It is reported that high voluminous structures out of NCs, which also partly possess the properties of their respective colloidal solution, can be achieved [16,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the fabrication methods for these kinds of structures are tedious and intrinsically limited, thus calling for novel preparation methods that could be applied to other metallic NCs. A way to overcome these problems could be hydro-or aerogelation of metals and metal oxides [14][15][16][17][18]. It is reported that high voluminous structures out of NCs, which also partly possess the properties of their respective colloidal solution, can be achieved [16,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Citrate and cyclodextrin are frequently utilized as the stabilizers to narrow the size distribution of the metal NPs. [44] The relatively weak coordination interaction between the stabilizer and metal NPs is critical for the gelation step (from B1 to H1 in Figure 1), which can be realized via an spontaneous gelation process [25,26,38] or via controlled destabilizations (by heating [45] or adding salt [46] and cross-linkers [47] Besides the porous and interconnected 3D network structure, hierarchical aerogels also possess backbones with locally modified morphologies instead of solid nanochains. As shown in Figure 1, this sub-structure can be obtained either by tailoring the hydrogel via strategy II (B1-H1-H2-A2) [43] or engineering the NBBs via strategy III (B1-B2-H3-A3).…”
Section: Synthesis and Featuresmentioning
confidence: 99%
“…The nanowirelike backbones are derived from the fusion and connection of the particulate NBBs (mostly noble metal NPs) during the gelation process. Depending on the elemental composition and distribution, these aerogels can be divided into three types: monometallic aerogels (Pd, Pt, Au, Ag), [38,39,46,47] bimetallic alloy aerogels (Pd x Pt y , Pt x Ni, Pt x Cu, etc), [25,26,49] and mixed multi/bimetallic aerogels (Au-Pd, Pd-Pt, Au-Ag-Pt, etc.). [45,50] Figure 2 shows the representative scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images of the wire-based aerogels.…”
Section: Wire-based Aerogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since a technique was introduced very recently to make aerogels from metal chalcogenide nanoparticles (Eychmüller 2005;Mohanan et al 2005;, 2007aBrock et al 2006;Bag et al 2007Gaponik et al 2008), a lot of effort has been made to create monoliths from nanoparticles. A variation of this technique was recently applied to sols of metal nanoparticles by Bigall et al (2009). While previous approaches for metal aerogels were based on the modification of oxide-based aerogels with metal nanoparticles for obtaining highly catalytically active materials (Pajonk 1997;Hüsing & Schubert 1998;Campbell 2004;Jiang & Gao 2006;Vallribera & Molins 2008), with this approach the resulting highly porous macroscopic monoliths are completely non-supportedly built only from metal nanoparticles.…”
Section: Hydrogels and Aerogels From Noble Metal Nanoparticlesmentioning
confidence: 99%